State of Implementation of Supply Chain Management in Companies in Romania - Cristinel Vasiliu; Mihaela Dobrea (Amfiteatru Economic Journal, 2013)
The aim of this study was to assess the degree of supply chain management's development in Romanian companies. For this, a selective, explorative survey, on a sample of 225 Romanian companies was used. The objectives of the research focused on highlighting the importance of logistics in the companies' management and on identifying specific issues related to supply chain management - role, objectives, predisposing factors, applications. From the research, it was found that supply chain management is at an early stage of development, specifically for the 80s and 90s. In addition, there is insufficient awareness that SCM is a tool for increasing business performance and competitiveness in the global market. The value of the study is given also by the fact that it is a pioneering work in Romania, where there were little such researches, especially in PhD thesis.
Keywords: F14; M19; N7; 330; Supply chain management (SCM); logistics; performances of companies; logistic cooperation; integration of firm's activities; global market; competitiveness